ANALISIS ARSITEKTUR HIJAU PADA BANGUNAN GEDUNG KEWIRAUSAHAAN UNIVERSITAS NEGERI SEMARANG - Pratiwi, Isna; Wicaksono, Dimas; Indarti, Fitri Dwi (Universitas Medan Area, 2024)
This study discusses implementing green architecture principles in the Business center building located in the campus environment in Semarang City. This study arises from the many business centers in Semarang that function as economic support. However, the construction of these buildings generally needs to consider the surrounding climate and environmental conditions. The research focuses on applying green architecture building principles, especially the Semarang State University business center building. The primary purpose of this study is to identify and then explain the principles of green architecture concepts and their application in the Entrepreneurship Building building at Semarang State University. In this study, applying a qualitative descriptive approach, researchers analyzed and applied the principles of green architecture concepts in the Semarang State University Entrepreneurship Building building. The results showed that the business center building analyzed had already been designed by taking into account the conditions of the surrounding natural environment, using environmentally friendly materials, and applying the concept of green architecture. Similarly, this building also applies energy conservation techniques that align with the vision and mission of Semarang State University and has an impact on supporting the preservation of the environment around the Entrepreneurship Building, meeting the needs of the community in it, and using the Entrepreneurship Building building